Atherogenic indices and smoking habits in cigarette smokers - Ayu Agbecha; Ameh Emmanuel Ameh (Wolters Kluwer Medknow Publications, 2018)
Background and Objective: Dyslipidemia is a mechanistic factor between cigarette smoking and cardiovascular diseases (CVD). Normolipidemic smokers may still be at risk of CVD, hence the need to better characterize serum lipids with atherogenic indices. This study aimed at determining atherogenic indices in relation to smoking habits in cigarette smokers. Materials and Methods: The case-control study compared lipid indices of sixty male smokers with six anthropometrically matched non-smokers. Three comparable subgroups of smoking habits were statistically tested. Associations of serum lipids, atherogenic indices, and smoking habits were also determined. Results: Significant high (P < 0.001) atherogenic indices, proatherogenic lipids (total cholesterol, triglycerides, low-density lipoprotein cholesterol (LDL-c), very LDL-c, non-high-density lipoprotein cholesterol [HDL-c]), and significant low (P < 0.001) HDL-c were observed in smokers compared to controls. Significant differences (P < 0.002) in serum lipids and atherogenic indices were observed within the subgroups of cigarette sticks smoked per day. Significant positive (P < 0.002) correlation of cigarette sticks smoked per day with proatherogenic lipids and atherogenic indices was observed in smokers, whereas significant inverse (P < 0.001) correlation was observed with HDL-c. Conclusion: Atherogenic indices proved to be a better predictor of cardiovascular risk, especially in settings of seeming normal lipid profile.